Ministry of Finance Decree No. 360 of the year 2010 Amending Certain Provisions Of The Decree Of The Minister Of Finance No. 554 of the year 2007 On The Rules Implementing The Provisions Of The Social Insurance Law Promulgated By Law No. 79 of the year 1975 Issued on 31/5/2010 = وزارة المالية قرار رقم 360 لسنة 2010 بتعديل بعض أحكام قرار وزير المالية رقم 554 لسنة 2007 بشأن القواعد المنفذة لأحكام قانون التأمين الاجتماعى الصادر بالقانون رقم 79 لسنة 1975 صادر بتاريخ 31/5/2010 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.